Peran KPK (Komisi Penegak Kedisiplinan) dalam Meningkatkan Kedisiplinan dan Kejujuran Siswa di MA Nurul Jadid dan MA Negeri 1 Probolinggo - Nada Aini Rahmah (Aafiyah: Jurnal Multidisiplin Ilmu, 2023)
Broadly speaking. student discipline and honesty are two characters that must be instilled in students in order students have a more personality good. And the objectives of learning can be achieved easily. Komisi Penegak Kedisiplinan (KPK) is a forum that has a role in handling students who are in trouble, violating school rules or not. In this case the purpose of the formation farom the KPK, namely so that students can be better, especially in problems discipline and honesty. Research aims at the role of the Komisi Penegak Kedisiplinan (KPK) in improving the discipline and honesty of students at MA Nurul Jadid Paiton Probolinggo and MA Negeri 1 Probolinggo. And the strategies does the Komisi Penegak Kedisiplinan (KPK) in improving student discipline and honesty MA Nurul Jadid Paiton Probolinggo and MA Negeri 1 Probolinggo. and How the in implementation of the Komisi Penegak Kedisiplinan (KPK) impacts the improvement of discipline and honesty of students at MA Nurul Jadid Paiton Probolinggo and MA Negeri 1 Probolinggo. To answer of the problems, a qualitative method approach is used, with case study research types and multisite research designs. Subject in This research includes: Principals, KPK Teachers, and MA Nurul Jadid Students Paiton Probolinggo and MA Negeri 1 Probolinggo. Types of research through Technical the data collection used is Observation, Interview, and Documentation. In the analysis, it is carried out by giving meaning to the data that has been successful collected and it is from that meaning that conclusions can be drawn. Test check the validity of the data is carried out using data triagulation, namely comparing results of direct observation (observation) with interview data and results that Associated.